Kemampuan Koneksi Matematis Siswa dalam Pembelajaran Matematika di Tingkat SMP - Petrus Srianto Mone; Juliana M. H. Nenohai; Damianus D. Samo (Universitas Nusa Cendana, 2022)
Abstract Mathematics is a science with a broad concept. The breadth of concepts in mathematics, does not rule out the possibility that these concepts are interrelated. For example, in studying linear equations with one variable, students must first know the concept of algebraic operations. This study aims to describe the concept of mathematical connection ability, describe the learning strategies used to improve the mathematical connection skills of junior high school students, and provide an overview of learning designs to improve mathematical connection skills for junior high school students. The method used by the author is a literature review method. Based on the studies conducted, it can be concluded that the ability of mathematical connection is the ability of students to relate between topics in mathematics and then mathematics topics with other sciences or with everyday life. The strategy or model used in learning mathematics is an important part for an educator in planning learning designs that will be applied in the learning process. Therefore, it is important for further researchers to apply existing strategies or models to different materials, so that they can be studied further about students' connection abilities in the learning process. Keywords: connection ability